Measuring outcomes for neurological disorders: a review of disease-specific health status instruments for three degenerative neurological conditions. - Heffernan, C; Jenkinson, C (2005)
Health-related quality-of-life measures have been increasingly used in research into neurological disorders in recent years. The aim of this paper is to provide an objective appraisal of the evidence in regard to disease-specific quality-of-life measures used in research on health interventions for three degenerative neurological disorders: multiple sclerosis, motor neurone disease/amyotrophic lateral sclerosis and Parkinson's disease. A comprehensive search strategy was developed to include nine relevant electronic databases. Only studies pertaining to patient-based outcome measurements in multiple sclerosis, motor neurone disease and Parkinson's disease were included. We identified 76 eligible studies. As studies consisted of descriptive and cross-sectional survey study designs, results were reported qualitatively rather than in the form of a meta-analysis. Four disease-specific measures were found for Parkinson's disease, 11 for multiple sclerosis and one for motor neurone disease. We conclude that health-related quality-of-life measures are useful in assessing the impact of treatments and interventions for neurological disorders. However, further research is needed on the development of instruments using psychometric methods and on the validation, utilization and responsiveness of instruments to change.